Children with hashimoto's thyroiditis have increased intestinal permeability: Results of a pilot study - Küçükemre Aydın, Banu; Yıldız, Melek; Akgün, Abdurrahman; Topal, Neval; Adal, Erdal; Önal, Hasan (Galenos Yayıncılık, 2020)
Increased intestinal permeability (IIP) precedes several autoimmune disorders. Although Hashimoto's thyroiditis (HT) is the most common autoimmune disorder, the role of HP in its pathogenesis had received little attention. Zonulin plays a critical role in IIP by modulating intracellular tight junctions. Rise of serum zonulin levels were shown to indicate HP in human subjects. In this case-control study, we examined the hypothesis that patients with HT have IIP. We studied 30 children and adolescents with HT, and 30 patients with congenital hypothyroidism (CH) matched for age, gender and body mass index (BMI). Serum zonulin levels, free thyroxine (fT4), thyroid stimulating hormone (TSH), anti-thyroglobulin antibody and anti-thyroid peroxidase antibody were measured. Zonulin levels were significantly higher in patients with HT than patients with CH (59.1 +/- 22.9 ng/mL vs. 43.3 +/- 32.9 ng/mL, p = 0.035). In patients with HT, zonulin levels were positively correlated with weight (r = 0.406, p= 0.03), BMI (r = 0.486, p = 0.006) and levothyroxine dose (r = 0.463, p = 0.02). In patients with CH, zonulin levels were positively correlated with age (r = 0.475, p = 0.008), weight (r = 0.707, p< 0.001), BMI (r =0.872, p <0.001) and levothyroxine dose (r =0.485, p = 0.007). After adjusting for age, weight, TSH and fT4 levels, serum zonulin was only associated with levothyroxine dose in patients with HT (R-2 =0.36, p =0.05). In patients with CH, only weight was associated with zonulin levels (R-2 =0.62, p <0.001). In conclusion, higher zonulin levels in children and adolescents with HT suggested IIP in these patients. Additionally, the association between zonulin levels and levothyroxine dose might imply a relationship between serum zonulin and disease severity.
Keywords: Autoimmune Thyroiditis; Congenital Hypothyroidism; Zonulin; Increased Intestinal Permeability